Why Do We Ignore the Risk in Schooling Decisions? - Joop Hartog; Luis Diaz-Serrano (Center for Economic Studies and ifo Institute (CESifo), 2014)
While uncertainty abounds in almost any decision on investment in schooling, it is mostly ignored in research and virtually absent in labour economics text books. This paper documents the scope for risk, discusses the tough disentanglement of heterogeneity and risk, surveys the analytical models, laments the absence of a good workhorse model and points out the challenges worth tackling: document ex ante risk that investors face, develop a tractable and malleable analytical model and integrate the option of consumption smoothing in analytical and empirical work. Hedging labour market risk in the stock market can be safely ignored.
Keywords: I21; J22; J24; J31; 330